Implementation and optimization of a data protecting model on the Sunway TaihuLight supercomputer with heterogeneous many‐core processors. (27th August 2018) - Chen, Yuedan; Li, Kenli; Fei, Xiongwei; Quan, Zhe; Li, Keqin
Summary: With the rapid development of information technology, the security of massive amounts of digital data has attracted huge attention in recent years. The Advanced Encryption Standard (AES) algorithm and the Security Hash Algorithm 3 (SHA3) are extensively used as cryptographic algorithms for protecting the security of information. The Sunway TaihuLight, with massive heterogeneous many‐core SW26010 processors, has the peak performance of over 100 PFlops. To achieve high efficiency of data encryption/decryption and guarantee the data integrity for large‐scale applications, this paper proposes a fast and secure data protecting model using the parallel AES algorithm and the SHA3 on the Sunway TaihuLight. According to the particular computing architecture and memory hierarchy of the Sunway TaihuLight, we propose a fine‐grained software design for the data protecting model to fully exploit the parallelism and properly arranges the data on the Sunway. Furthermore, we propose optimization strategies for the parallel AES algorithm of the data protecting model. It is proved that our data protecting model has high security, good scalability, and excellent encryption/decryption efficiency on the Sunway. Our data protecting model achieves a high throughput of 269.95 Gbits/s, and the optimized parallel AES algorithm achieves 511.28 Gbits/s on the Sunway.